Endoscopic drainage in patients with malignant extrahepatic biliary obstruction: when and how. Issue 10 (October 2020) - Mangiavillano, Benedetto; Papanikolaou, Ioannis S.; Arvanitakis, Marianna; Auriemma, Francesco; Bianchetti, Mario; Tarantino, Ilaria; Traina, Mario; Deviere, Jacques; Repici, Alessandro
Abstract : The question of when and how to drain a malignant biliary obstruction (MBO), both intrinsic or extrinsic, remains a controversial point among endoscopists. An important factor that influences the decision to drain an MBO or not is if the patient is a surgical candidate or not and, in the former case, if the patients must undergo neoadiuvant chemotherapy or not. Other questions arising during biliary drainage in MBO patients is which type of stent should be chosen, plastic or metal, and if endoscopic biliary sphincterotomy must be performed or not when a stent is placed. The present review attempts to answer these questions and summarizes the optimal approach toward patients with MBO based on the available evidence.